An oral M-cell targeted Lactococcus lactis vaccine against Echinococcus multilocularis infection - Xiao, Yang; Luo, Zhao-Hui; Wang, Shun-Juan; Dai, Yao; Chen, Jia-Yu; Cui, Jia-Yong; Li, Run-Le; Tang, Feng (Frontiers in Immunology, 2025)
BackgroundAlveolar Echinococcosis (AE) is a serious infectious disease caused by Echinococcus multilocularis (E.multilocularis,Em) in the highlands of northwestern China and vaccination is currently the most effective means of preventing E. multilocularis infection. However, current vaccines are not sufficiently effective in preventing and controlling Alveolar Echinococcosis.MethodsIn this study, an oral M-cell targeted Lactococcus lactis (L. lactis) vaccine (LL-plSAM-GILE) was constructed by adding SAM gene sequence to the epitope vaccine GILE for E. multilocularis constructed in our previous study. Mice were orally immunized with LL-plSAM-GILE and their serum antibody levels (ELISA), lymphocyte proliferation (MTS), IFN-γ levels (ELISpot), IL-4 levels (flow cytometry, FCM), T cells (FCM), growth of hepatic cysts (Ultrasound), and weights were measured to evaluate the protective effect of LL-plSAM-GILE.ResultsThe L.lactis expression plasmid pNZ8148-SAM-GILE was successfully constructed and electroporated into L.lactis NZ9000, and the recombinant protein was approximately 45 KD. SAM-GILE was expressed on the surface of recombinant L.lactis. LL-plSAM-GILE is effective in targeting Microfold cells. Mice immunized with LL-plSAM-GILE exhibited significantly elevated levels of specific IgG antibodies. Lymphocyte proliferation was enhanced compared to the control group and the NZ9000 group. LL-plSAM-GILE stimulated the production of CD4+ and CD8+ T cells. Mice immunized with LL-plSAM-GILE secreted more IFN-γ and IL-4. For both primary and secondary infections, oral immunization with LL-plSAM-GILE led to a significant decrease in the diameter and weight of hepatic cysts.ConclusionsAn oral M-cell targeted L.lactis vaccine LL-plSAM-GILE with excellent immunogenic and immunoprotective properties has been successfully constructed. This study may provide important theoretical and experimental bases for the prevention and treatment of E. multilocularis infection.